(untitled) (Comunicação & Inovação, 2021)
This paper outlines some conditions for the circulation of scientific knowledge in Communication grounded on the area’s main journals. It studies the themes, geographical and chronological distribution and publication rules of 52 magazines. Analysis has shown three main characteristics: (1) publications responsible for the formation of the Area’s scientific capital; (2) 82% of publications discuss communication interfaces with other areas, in a wide range of subjects; (3) the publication of doctors (or in co-authorship with doctors) is the majority: only 17% of the journals make room for individual publications of other titles.